THE EFFECT OF APPLYING DISCUSSION STRATEGY ON STUDENTS’ ACHIEVEMENT IN WRITING DESCRIPTIVE TEXT - Saidatul Hanim; Rahmah (Universitas Negeri Medan, 2014)
The objective of the study is to discover the effect of applying Discussion Strategy on students’ achievement in writing descriptive text. The study was conducted by using experimental research design. The samples were taken by using random technique through lottery and two out of 7 classes were taken into samples, X-1 as experimental group was taught Discussion Strategy and X-3 as control group was taught Conventional Strategy, each class has 30 students. The instrument for collecting the data was writing test. The data were analyzed by using t-test formula. After analyzing the data, it was found that the value of t0 (3,561) with the degree of freedom (df)=58 at the level of significance p (0,05) = 2,004. It means that t0 was considerably higher than tt (3,561 > 2,004). The result showed that Discussion Strategy had a significant effect on students’ writing achievement. So, the alternative hypothesis (Ha) is accepted.